Manajemen Pondok Pesantren Sabrun Jamil dalam Pembinaan Kader Da’i di Bone Bolango - Kango, Andries; Perdana, Dian Adi; Udjani, Meta; Caco, Rahmawati (Tadbir: Jurnal Manajemen Dakwah, 2024)
The aim of this research is to find out about the management of the Sabrun Jamil Islamic Boarding School in developing da’i cadres. This research uses qualitative research with data obtained from documentation, interviews and observations and literature related to research materials. Data obtained from respondents, informants and documents are then processed through editing processes, data classification and data interpretation. The results of this research are that the Sabrun Jamil Islamic Boarding School, Botupingge District, in developing da’i cadres, is in accordance with the management principles: Planning, Organizing, Mobilizing and Supervising. There are two forms of training for da’i cadres at the Sabrun Jamil Islamic Boarding School, Botupingge District, namely: First, training in the Islamic boarding school, in the form of short lectures (kultum), yellow book studies, barzanji reading, sholawatan, reciting the Koran and other Islamic studies. Second, coaching da’i cadres to go directly into the community in the Sabrun Jamil Islamic Boarding School program called PPM (Community Service Practice) and PPL (Field Service Practice). The obstacles experienced in developing da`i cadres are the qualifications of the ustadz which do not match their field of preaching expertise, and the santri who are still unfamiliar with the knowledge of the Islamic religion. The solution in terms of developing da’i cadres at the Sabrun Jamil Islamic Boarding School is to bring in ustadz who have Islamic knowledge with qualifications in the fields of aqidah, morals, Islamic law and have a passion for preaching. The students are directed by the Ustadz to become da’i cadres who understand the concept of da’wah (amar ma`ruf nahi munkar).